Penerapan Model Discovery Learning Untuk Meningkatkan Keaktifan Siswa Dalam Pembelajaran Menganalisis Struktur Teks Laporan Hasil Observasi - Marlina, Marlina; Haliq, Abdul; Hapida, Hapida (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to increase students' activeness in analysing the structure of observation report text through the application of Discovery Learning model at SMA Negeri 21 Makassar. The method used is Classroom Action Research with two cycles, each including planning, action, observation, and reflection. Data collected from cycle I and II will be analysed using qualitative and quantitative analysis. The results showed that students' activeness increased significantly, seen from the percentage of aspects of asking questions (50% to 75%) and expressing opinions (33.3% to 66.7%). The average score of students' learning outcomes also increased from 68 in the first cycle to 80 in the second cycle, with the level of learning completeness reaching 83.3%. Reflection on each cycle showed that strategies such as the use of interactive media and reinforcement of instructions were effective in increasing learner activeness. Thus, the Discovery Learning model was proven effective in improving learner engagement and learning outcomes, and is relevant to be applied in 21st century learning.